PRAKTIK PREDATORY PRICING DALAM SEKTOR E-COMMERCE: TINJAUAN TERHADAP UNDANG-UNDANG NOMOR 5 TAHUN 1999 - Oktaviani, Tri; Pribadi, Deny Slamet; Utomo, Setiyo (Universitas Labuhanbatu, 2025)
The rise of digital business and technological advancement has shifted conventional economic practices to digital platforms, with e-commerce often dominated by companies using strategies like predatory pricing to maintain market control. Such practices, including flash sales and free shipping, are challenging to regulate due to difficulties in gathering sufficient evidence. This study employs a socio-legal research method, with data from interviews and legal materials, identifying three key indicators of predatory pricing: sales below production cost, competitor exit, and subsequent price increases. Although Indonesia's Business Competition Supervisory Commission (KPPU) enforces competition laws, evidence challenges and legal interpretation complexities remain. Policy reform and capacity-building efforts are essential for effective oversight in this evolving digital landscape.Keywords: E-commerce;Legal Supervision;Predatory Pricing